The state of individual components of humoral immunity of guinea pig blood in the dynamics of the formation of experimental periodontitis and immobilization stress and correction of their disorders by thiocetam - Regeda, M.; Olekshij, P. (Journal of Education, Health and Sport, 2022)
The research found a rapid increase in the level of immunoglobulin M, starting from the 3 rd day of the experiment in comparison with the control values, which clearly indicates its activation in particular, and stimulation of humoral immunity in general. In the later stages (on the 5 th and 15 th days) of the formation of experimental periodontitis (EP) and immobilization stress (IS), an increase of this indicator by 93.5% and 94.2% was found, respectively, against group I guinea pigs (p≤0, 05).Regarding the content of immunoglobulin G in the blood, the highest growth rates were recorded in the fourth group of guinea pigs with EP and IS (on the 15 th day), which indicates a direct dependence of the duration of damaging factors on the level of these indicators and the body’s ability to the protective response. The results of the treatment showed the effect and the reduction of the activity of the studied classes of immunoglobulins. Thus, the use of thiocetam led to a significant decrease in the content of Ig M and G in the blood, respectively, by 33.8% (p1≤0.05) and 41.7% (p1≤0.05) in EP and IS compared with the group of animals were not exposed to this drug, which indicates the immunocorrective effect of this drug on the studied tests.